Non-verbal communication of German language in a German film: A Coffee in Berlin - Farhana Farid,; Roslina Mamat, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Non-verbal behaviour is very important in conversations, yet it is not given much attention. Foreign language learners who are not exposed to these pivotal non-verbal communications will find it difficult to recognise it during a conversation which consequently could lead to confusion. In addition, it will also affect the flow of the conversation especially among language learners that have less access to real language situations or native speakers. This article begins with analysing a German language conversation in a German film “A Coffee in Berlin” by Jan Ole Gerster, to detect the non-verbal turn-taking signals as well as to interpret the function and purpose of the signals based on the Stenstrom’s theory (1994) of turn-taking. This article uses Gesprächsanalytisches Transkriptionssystem 2 (discourse and conversation- analytic transcription 2) or also recognised as GAT 2 by Selting (2009) for the data transcription as it is highly adaptable in transcribing data of German language to detect the non-verbal turn-taking signals in the conversation. Qualitative descriptive is chosen as the method of this study as it is detailed, comprehensive and makes sense to the reader. Using the method and theories stated bring results of the non-verbal turn-taking signals such as gaze, gestures and facial expression which are used in German conversation when yielding, continuing and taking the floor of conversation.